Effect of Firing Temperature on Density, Porosity, Impact Strength, and Macro Structure of Crucible Materials Made from Graphite, Kaolin, and Castable Cement - Latif, Abdul; Rusiyanto, Rusiyanto; Sunyoto, Sunyoto; Kriswanto, Kriswanto; Fitriyana, Deni Fajar (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2022)
Along with the advancement of modern times and technology, the metal sector plays a critical role in sustaining present growth. The industry's increased competitiveness has hampered the development of numerous small-scale metal casting industries. A crucible made of local graphite can only be used not more than ten melting cycles. This research aims to examine the influence of firing temperature on the density, porosity, impact strength, and macrostructure of graphite, kaolin and castable cement crucible materials. This research applies experiment method at various firing temperature, i.e. 850 °C, 900 °C, 950 °C, 1000 °C and 1050 °C. The crucible materials are made of graphite, kaolin, and castable cement. The firing process employs a heating rate of 5 °C/min and a holding time 2 hours. The results show that firing temperature influences the density, porosity, impact strength and macrostructure of crucible. The highest density at 1.86 grams/cm3 was obtained at the firing temperature of 1050 °C. The lowest porosity value of 41% was attained at firing temperature of 1050 °C. However, this value was still below the crucible index criterion. The highest impact strength of 0.003249 Joule/mm2 occurred for firing temperature of 1050 °C.